Leptin and its receptor: can they help to differentiate chromophobe renal cell carcinoma from renal oncocytoma? - Ng, Keng Lim; Del Vecchio, Sharon Juliet; Samaratunga, Hemamali; Morais, Christudas; Rajandram, Retnagowri; Vesey, David A.; Wood, Simon Thomas; Gobe, Glenda Carolyn (Lippincott Williams & Wilkins, 2018)
One of the challenges in differentiating chromophobe renal cell carcinoma (chRCC) from benign renal oncocytoma (RO) is overlapping morphology between the two subtypes. The aim of this study was to investigate the usefulness of expression of leptin (Ob) and its receptor (ObR) in discriminating chRCC from RO. Sections from paraffin-embedded, formalin-fixed tumour nephrectomy specimens of 45 patients, made up of 30 chRCC (15 eosinophilic variant and 15 non-eosinophilic variant) and 15 RO, were used in this study. Samples (30) of clear cell RCC (ccRCC), the most common histological subtype, were used to verify staining patterns found by others in our cohort of Australasian patients. Matched morphologically normal non-cancer kidney tissues were included for each specimen. Sections were batch-immunostained using antibodies against Ob and ObR. Stained sections were digitally scanned using Aperio ImageScope, and the expression pattern of Ob and ObR was studied. In this cohort, male to female ratio was 2:1; median age was 64 (45–88 years); and median tumour size was 3.8 cm (range 1.2–18 cm). There were 47 (62.7%) T1, seven T2, 20 T3 and one T4 stage RCC. Two patients with ccRCC presented with metastases. Nuclear expression of Ob was significantly higher in RO compared with chRCC. The increased nuclear expression of Ob in RO compared with chRCC may be a useful aid in the difficult histological differentiation of RO from chRCC, especially eosinophilic variants of chRCC.